Comparison of State Administration Management between Egypt and Indonesia - Rafian, Ziddane; Maritza, Dhiya Fariyyah; Lina, Rafel; Latifah, Mawadah; Mahfira, Saila (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2024)
Comparison of state administration is carried out as tips for improving a country towards an effective and efficient form and management of government in bringing the country towards prosperity and progress. The comparative science of state administration has a function as a benchmark in management and problem-solving. Egypt and Indonesia have a variety of unique things to compare and study. This research studies the state administration of Egypt and Indonesia which includes the form of the state, government system, political system, political infrastructure as well as the factors that underlie the creation of state administration such as social factors, moral factors, cultural factors and territorial factors. Differences and similarities were found in the comparisons prepared using this literature study method, such as similarities in the government system which is divided into regions that have their own authority and autonomous powers. There are also similarities in the political system which adheres to the freedom of many parties to participate in becoming candidates for government institutions such as the legislative body and heads of state or regions such as the President. The differences can be seen in the government system, Indonesia uses a presidential government system while Egypt uses a semi-presidential government system.